CLINICAL IMPORTANCE OF ENDOTHELIAL DYSFUNCTION AND INSULIN RESISTANCE SYNDROME IN PATIENTS WITH GOUT ASSOCIATED WITH ARTERIAL HYPERTENSION - N. N. Kushnarenko; A. V. Govorin (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study the endothelium status and determine the correlation between endothelial dysfunction and glucose metabolism in men with gout associated with arterial hypertension (HT). Material and methods. Patients (n=175, all are males) with gout were enrolled into the study. Ambulatory blood pressure monitoring (ABPM) was performed in all patients. Endothelial function was studied in tests with reactive hyperemia (endothelium-dependent reaction) and nitroglycerin (endothelium independent reaction) in brachial artery by ultrasonic Doppler examination. The level of nitrite-nitrate and endothelin-1 in blood serum was determined by ELISA technique. Fasting blood glucose and oral glucose tolerance tests were performed as well as fasting insulin blood level was determined by immunoenzyme method. Insulin-resistance index (HOMA-IR) was calculated. Patients with HOMA- IR>2.77 were considered as insulin-resistant. Results. Patients with gout demonstrated endothelial deterioration associated with activation of nitroxid producing function, elevation in endothelin-1 serum level (1.36 fmol/ml [0.91; 2.32 fmol/ml] vs 0.19 fmol/ml [0.16; 0.27 fmol/ml] in controls, p<0.05) and impairments of endothelium-dependent vasodilation (6.4% [3.3; 7.3%] vs 17.8% [12.7; 23.9%] in controls, p<0.05). The revealed changes were the most marked in patients with gout associated with HT. The correlation between some endothelial dysfunction in- dices and glucose metabolism was observed. Conclusion. ABPM, brachial artery endothelium-dependent vasodilation and glucose metabolism status should be studied in patients with gout. Complex treatment of cardiovascular diseases in patients with gout should include ω-3 polyunsaturated fatty acids, angiotensin receptor antagonists should be used for antihypertensive therapy.